Potency and selectivity of a urokinase activated recombinant anthrax toxin to acute myeloid leukemia (AML) cells. (c2015) - Darwich, Manal El. (2016)
Acute myeloid leukemia (AML) is a disorder characterized by uncontrolled mitogenetic activation and proliferation of hematopoietic precursor cells. Up to 30 % of adult patients with AML do not achieve complete remission when treated using chemotherapy. In addition, severe side effects usually limit the efficacy of available therapeutic approaches. As a result, novel tumor-selective therapeutics capable of targeting and eliminating AML blasts while sparing normal cells are urgently needed. In this study, we determine the potency and selectivity of an engineered, urokinase-activated recombinant anthrax fusion toxin (PrAgU2/FP59) on a panel of 9 AML cell lines and on normal progenitor bone marrow blasts. All 9 AML cell lines tested were sensitive to PrAgU2/FP59 while normal progenitor, bone marrow blasts were not, demonstrating the potency and selectivity of this tumor-targeted approach. Cytotoxicity of PrAgU2/FP59 appeared to be non-apoptotic and is dependent on the expression of an active cell surface urokinase plasminogen activator system (uPA/uPAR) system. Targeting the urokinase system, a protease overexpressed on AML cells, appears to be a promising approach for the development of AML-specific therapeutics.